Polymethylmethacrylate-induced inflammatory macrophages resorb bone. - Quinn, J; Joyner, C; Triffitt, J; Athanasou, N (1992)
Macrophages and their fused products are commonly found at the polymethylmethacrylate cement-bone interface, but it is not known if they contribute directly to the osteolysis associated with loosening of the cemented prosthesis. We isolated mononuclear phagocytes from granulomas formed by subcutaneous implantation of polymethylmethacrylate into mice and incubated them on bone slices in which they formed resorption lacunae after co-culture for seven to 14 days with both marrow stromal cells and osteoblast-like cells (in the presence of 1 alpha,25-dihydroxyvitamin D3 and dexamethasone). Increased numbers of tartrate-resistant acid phosphatase-positive mononuclear and multinucleated cells formed in these cultures. Both in the presence and absence of stromal cells, macrophages produced extensive superficial roughening of the bone surface. Polymethylmethacrylate-induced macrophages are thus capable of low-grade surface and high-grade lacunar osteolysis, the latter requiring the presence of specific hormonal and stromal cell elements. These two forms of bone resorption could account for the pathogenesis and clinical patterns associated with loosening of the cemented prosthesis.